Is genetic involve in the outcomes of contact reactions between parent and offspring and between siblings of the coral Pocillopora damicornis? - Diah Permata Wijayanti; Michio Hidaka (Marine Science Department Diponegoro University, 2018)
Various allogeneic responses have been characterized in stony corals. The responses were thought to be genetically control. However, very little is known about the genetic mechanism of allorecognition in corals. Therefore, the contact reaction between parent-offspring and between siblings of the coral Pocillopora damicornis has been studied. Three types of contact reactions were observed: between young colonies, between adult and young colonies, and between adult colonies. Siblings, which were primary polyps or young colonies derived from the same broodparent, invariably fused. All but one pair of parent-offspring grafts exhibited fusion. However, some pairs of young colonies derived from the same two broodparents showed a different contact response than did the broodparents when their branch tips were paired. When the same pairs of the young colonies were repeated to contact at different age, most pairs yielded the same results. Together with the findings that young colonies were able to recognize their partner less than 1 month after the initial contact, we suggest that contact reaction in coral and time needed for the stable reaction are most probably under genetic control. Keywords: coral, young colonies, reproduction, parent-offspring relationship, histocompatibility